The non-sleepy neurotic: The role of a good night’s sleep for daily self-regulatory resources and vitality at work - Junça Silva, A.; Mosteo, L.; Rueff, R. (International Journal of Organizational Analysis, 2024)
Purpose: Relying on the effort-recovery model, this study aimed to test how and when a good night’s sleep increases in daily physical health. The authors hypothesized that when individuals have a good night’s sleep, it helps them to recover their self-regulatory resources, and, in turn, these cognitive resources improve their physical health experienced at work. Furthermore, the authors argue that this will be different depending on the individuals’ levels of neuroticism; that is, the indirect relationship between sleep duration and physical health through self-regulatory resources will be stronger for individuals who score lower on neuroticism, and in contrast, the relationship will be buffered for those who score higher on neuroticism. Design/methodology/approach: To test the hypothesized model, the authors conducted a three-wave longitudinal study with working adults (N = 262). The authors used multilevel modelling to test if neuroticism moderated the indirect relationship between sleep duration and physical health through self-regulatory resources, at both between and within-person levels. Findings: The multilevel results showed that a good night’s sleep recovered self-regulatory resources needed to promote physical health; however, this indirect relationship was buffered for those who scored higher on neuroticism (versus lower levels of neuroticism). Practical implications: Hence, the role of neuroticism as a potentially harming condition for employees’ physical health is pointed out. Originality/value: The findings highlight the relevance of sleep as a recovery activity for both cognitive and physical resources experienced during the working day. However, this appears to be attenuated for employees with higher levels of neuroticism.